A method for preparing tin dioxide powder by freeze drying to inhibit tin hydroxide agglomeration

By combining ultra-low temperature rapid freezing and low temperature high vacuum sublimation drying, the agglomeration problem of tin hydroxide during the freeze-drying process was solved, and highly dispersed and high-purity tin dioxide powder was prepared, which is suitable for electronic-grade materials.

CN122355336APending Publication Date: 2026-07-10YUNNAN TIN INDIUM LAB CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202610662639.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-05-14
Publication Date
2026-07-10

Smart Images

  • Figure CN122355336A_ABST
    Figure CN122355336A_ABST
Patent Text Reader

Abstract

This invention discloses a method for preparing tin dioxide powder by freeze-drying to inhibit tin hydroxide agglomeration. The method involves adding a tin source solution (36-54 g / L) and a precipitant solution (5-30 g / L) at a mass ratio of 1:0.1-0.25 under constant temperature and magnetic stirring. The precipitant solution is then added dropwise to the tin source solution, reacting to form tin hydroxide colloid. After static aging, the colloid undergoes rapid cryogenic freezing to instantly freeze it into an ice state. The ice-state colloid is then subjected to low-temperature vacuum sublimation drying to obtain loose tin hydroxide dry powder. The dry powder is then calcined to obtain tin dioxide powder. This invention fundamentally eliminates the agglomeration of tin dioxide powder, resulting in tin hydroxide dry powder with an agglomeration rate of less than 10% and a purity of over 99.9%, providing a high-quality precursor for high-performance electronic-grade tin dioxide.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of inorganic material preparation technology, specifically relating to a method for preparing nano-tin dioxide powder. Background Technology

[0002] Tin hydroxide [Sn(OH)4], as an important precursor for the preparation of tin dioxide (SnO2), has wide applications in the preparation of nano / ultrafine inorganic functional materials. Due to its excellent optical, electrical, and gas-sensitive properties, tin dioxide is widely used in gas sensors, transparent conductive films, lithium-ion battery anode materials, and electronic ceramics. With the rapid development of the electronics and information industry, increasingly stringent requirements have been placed on the particle size, dispersibility, and purity of tin dioxide powder, and the drying quality of its precursor, tin hydroxide, directly determines the performance of the final tin dioxide product.

[0003] However, tin hydroxide colloids or slurries face severe agglomeration problems during the drying process, which has always been a key technical bottleneck restricting the preparation of high-performance tin dioxide. Existing drying methods, such as oven drying and spray drying, often fail to effectively solve this problem. For example, during oven drying, water evaporation generates significant capillary forces, causing particles to come close together and form robust liquid bridges, which then transform into hard agglomerates that are difficult to disperse. While spray drying can reduce agglomeration to some extent, for nanoscale tin hydroxide colloids, the surface tension of the droplets still leads to particle aggregation, forming hollow spheres or agglomerates, and the equipment is expensive and energy-intensive. Freeze-drying technology, by freezing the water in the substance first and then directly sublimating it, theoretically bypasses the liquid phase stage and avoids the effects of capillary forces, thus being considered an ideal method for preparing highly dispersed nanopowders. However, the conventional direct freeze-drying method is not ideal when applied to pure tin hydroxide colloids. The problem is that if the freezing rate is insufficient (such as using a conventional freezer at -20°C), ice crystals will grow slowly and compress the colloidal particles, destroying their original dispersion state and causing "freeze agglomeration". If the temperature or vacuum parameters in the subsequent sublimation drying stage are not matched, some ice crystals may melt or undergo secondary crystallization, which will also cause serious agglomeration problems.

[0004] To address the aforementioned issues, researchers both domestically and internationally have conducted extensive research. Chinese patent CN103263963 A discloses a method for producing ultrafine nano-powder using a wet-to-dry process without dispersants. This method involves freezing the material to below -68°C and then subjecting it to vacuum sublimation drying, resulting in loose, non-agglomerated nano-sized mineral powder. However, this method processes mineral slurries (such as barite and quartz) obtained through wet grinding, employing a physical dispersion process. For nano-sized tin hydroxide colloids synthesized via chemical precipitation, due to the large number of hydroxyl groups on their particle surface and extremely high surface energy, the agglomeration tendency during freezing and drying is far stronger than that of physically ground micron-sized mineral particles. Therefore, there are fundamental differences between physically ground micron-sized mineral particles and chemically precipitated nano-sized tin hydroxide colloids in terms of particle surface properties, stability, and crystallization behavior during freezing. Furthermore, CN103263963 A only provides a broad range of freezing temperatures below -68℃, without disclosing specific sublimation drying temperatures and vacuum parameters, nor does it disclose the subsequent calcination treatment steps to convert hydroxides into oxides, making it unsuitable for direct application in the preparation of electronic-grade tin dioxide.

[0005] Other existing related technologies also have their limitations. CN120117648 A discloses a method for preparing tin dioxide powder, which achieves zero wastewater discharge through steps such as adding composite additives and ultrasonic dispersion. However, it requires optimization of the type and ratio of composite additives to improve the dispersibility of tin, and the introduced organic additives can affect the purity of the product. CN114314642A discloses a method for preparing ultra-dispersed ITO powder, which uses liquid nitrogen pre-freezing combined with the action of dispersants to obtain low-agglomeration powder. However, the liquid nitrogen pre-freezing process is complex and costly, and the introduction of dispersants can cause carbon residue problems in the subsequent calcination process. CN115974139 A discloses a method for preparing highly efficient dispersed SnO2, which uses liquid nitrogen freezing. However, its treatment target is already agglomerated SnO2 powder, and its purpose is to "break up" the formed agglomerates rather than prevent agglomeration. Although CN103482616B and CN 104143631B also involve tin dioxide and freeze drying, they prepare graphene / tin dioxide composite materials. In these systems, graphene itself plays a role in separating and inhibiting agglomeration, and cannot be directly transferred to the drying process of tin hydroxide colloids. Summary of the Invention

[0006] The purpose of this invention is to overcome the above-mentioned defects of the prior art and provide a method that does not require the addition of dispersants, has a reasonable process, is simple and efficient, and can effectively inhibit the agglomeration of tin hydroxide during drying.

[0007] To achieve the above objectives, the present invention adopts the following technical solution: A method for preparing tin dioxide powder with anti-tin hydroxide agglomeration by freeze drying includes the following steps: (1) Preparation of tin hydroxide colloid: Sodium stannate is dissolved in deionized water with a conductivity ≤10μS / cm to prepare a tin source solution with a concentration of 36-54g / L; oxalic acid is dissolved in deionized water with a conductivity ≤10μS / cm to prepare a precipitant solution with a concentration of 5-30g / L; the mass ratio of tin source solution to precipitant solution is controlled at 1:0.1-0.25; under constant temperature magnetic stirring, the precipitant solution is added dropwise to the tin source solution at a rate of 1-2mL / min, the reaction temperature is controlled at 25-30℃, the stirring speed is controlled at 300-500r / min, and tin hydroxide colloid is generated by the reaction; after the reaction is completed, stirring is continued for at least 2h, and the mixture is allowed to stand for at least 24h to age, and the particle size of the colloid is controlled at 50-100nm; (2) Ultra-low temperature rapid freezing treatment: Transfer the aged tin hydroxide colloid in step (1) to a freezing container and place it in a cold trap at ≤-70℃±2℃ for rapid freezing for 30-60 minutes to freeze the colloid into an ice state instantly, thereby inhibiting the particle extrusion and agglomeration caused by ice crystal growth; (3) Low-temperature vacuum sublimation drying: The ice colloid after freezing in step (2) is transferred to a freeze dryer and sublimated at a temperature of -50℃±2℃ and a vacuum of 15±5Pa for 24-48h, so that the ice crystals sublimate directly, avoiding the generation of liquid phase during the drying process, and obtaining loose tin hydroxide dry powder. (4) Calcination treatment: The dry tin hydroxide powder after step (3) is placed in a muffle furnace and calcined at 900±20℃ for 3-5 hours to obtain tin dioxide powder.

[0008] Furthermore, the rapid freezing described in step (2) has a freezing rate of ≥10℃ / min.

[0009] Furthermore, the freezing container mentioned in step (2) is a polytetrafluoroethylene container.

[0010] Furthermore, in step (4), the calcination environment inside the muffle furnace is an air atmosphere with an oxygen content of ≥20%.

[0011] The core concept of this invention is to obtain stable, uniformly sized tin hydroxide colloid by controlling the mass ratio of tin source solution to precipitant solution at 1:0.1-0.25 in step (1). This mass ratio range is the optimal range obtained through extensive experimental optimization, ensuring that the size of the colloidal particles generated by the reaction is stable between 50-100 nm, and the surface hydroxyl content is moderate, providing a basic guarantee for the inhibition of polymerization during subsequent ultra-low temperature freezing and vacuum sublimation drying. If the mass ratio is lower than 1:0.1, insufficient precipitant will lead to incomplete reaction of sodium stannate; if the mass ratio is higher than 1:0.25, excessive oxalic acid will form a complex with tin hydroxide, affecting the stability of the colloid. The ultra-low temperature rapid freezing in step (2) achieves the "vitrification freezing" of the colloid, forming tiny and uniform ice crystals, which maximizes the fixation of the dispersion state of the colloidal particles, laying a good foundation for subsequent sublimation. Through the low-temperature high-vacuum sublimation drying in step (3), the frozen water can be steadily and completely sublimated directly into water vapor in a specific low-temperature high-vacuum environment, avoiding any form of liquid phase appearance throughout the process, thereby eliminating the capillary force that leads to agglomeration from the root.

[0012] This invention, through the synergistic effect of ultra-low temperature rapid freezing and low-temperature high-vacuum sublimation drying, effectively solves the agglomeration problem caused by slow freezing rate and mismatched drying parameters without adding any dispersant, obtaining highly dispersed and high-purity tin hydroxide dry powder. This provides a high-quality precursor for high-performance electronic-grade tin dioxide and further yields tin dioxide powder. Its beneficial effects are as follows: 1. Significant synergistic inhibition of agglomeration: This invention achieves agglomeration inhibition throughout the entire process from freezing to drying by synergistically combining "-75℃ ultra-low temperature rapid freezing" with "-50℃ / 15Pa low temperature high vacuum drying." The specific parameter combination is specially designed for the characteristics of the pure tin hydroxide colloidal system. Experimental data shows that the agglomeration rate of the tin hydroxide dry powder prepared by this method can be consistently below 10%, which is far superior to traditional oven drying (agglomeration rate > 50%) and conventional freeze drying at -20℃ (agglomeration rate > 30%), proving that the parameter combination produces a synergistic effect.

[0013] 2. High product purity and good dispersibility: Since no dispersants or organic modifiers are added throughout the process, the introduction of impurities is fundamentally avoided, resulting in a product purity of over 99.9%. Using tin hydroxide as a precursor, the calcined tin dioxide powder exhibits a uniform particle size distribution (D50 of 80-120 nm) and a large specific surface area (≥30 m² / g), fully meeting the stringent requirements of electronic-grade materials for high purity and high dispersibility.

[0014] 3. Simple process and easy to industrialize: This invention can be realized based on conventional freeze-drying equipment (only the cold trap temperature can reach -75℃ to -80℃). The process flow is simple, the parameter range of each step is wide, and it is easy to achieve precise control and large-scale production. It has significant industrialization advantages and cost benefits. Attached Figure Description

[0015] Figure 1 Scanning electron microscope (SEM) image of the loose tin hydroxide dry powder prepared before calcination for Example 1.

[0016] Figure 2 This is a particle size distribution diagram of the tin dioxide powder obtained after calcination in Example 1.

[0017] Figure 3 Comparison of the appearance of the tin hydroxide dry powder prepared by the conventional oven drying method (Comparative Example 1) and the conventional freeze drying method (Comparative Example 2) with the tin hydroxide dry powder obtained in Example 1. Detailed Implementation

[0018] The present invention will be further described in detail below through embodiments, but the scope of protection of the present invention is not limited to the embodiments.

[0019] The freeze-drying preparation method of tin dioxide powder for inhibiting tin hydroxide agglomeration according to the present invention comprises the following steps: Preparation of tin hydroxide colloid: Sodium stannate was dissolved in deionized water with a conductivity ≤10 μS / cm to prepare a tin source solution with a concentration of 36-54 g / L; oxalic acid was dissolved in deionized water with a conductivity ≤10 μS / cm to prepare a precipitant solution with a concentration of 15-30 g / L; the mass ratio of the tin source solution to the precipitant solution was controlled within the range of 1:0.1-0.25; under constant temperature magnetic stirring, the precipitant solution was added dropwise to the tin source solution at a rate of 1-2 mL / min, the reaction temperature was controlled at 25-30℃, and the stirring speed was controlled at 300-500 r / min, and tin hydroxide colloid was generated; after the reaction was completed, stirring was continued for 2 h, and the mixture was allowed to stand for aging for 24 h, controlling the particle size of the colloid to be 50-100 nm; Ultra-low temperature rapid freezing treatment: Transfer the aged tin hydroxide colloid from step (1) to a freezing container and place it in a cold trap at ≤-70℃ for rapid freezing for 30-60 minutes to freeze the colloid into an ice state instantly, so as to inhibit the particle extrusion and agglomeration caused by ice crystal growth; (3) Low-temperature vacuum sublimation drying: The ice colloid after freezing in step (2) is transferred to a freeze dryer and sublimated at a temperature of -50±2℃ and a vacuum of 15P±5Pa for 24-48h, so that the ice crystals sublimate directly, avoiding the generation of liquid phase during the drying process, and obtaining loose tin hydroxide dry powder. (4) Calcination treatment: The dry tin hydroxide powder after step (3) is placed in a muffle furnace and calcined at 900±20℃ for 3-5 hours to obtain tin dioxide powder.

[0020] Equipment and instrument parameters used: Thermostatic magnetic stirrer: Model B15-3 (Shanghai Sile Instrument Co., Ltd.), temperature control accuracy ±0.5℃; Freeze dryer: Model YTLG-10A (Shanghai Yetuo Technology Co., Ltd.), cold trap temperature minimum -80℃, vacuum degree adjustable range 1-100Pa; Muffle furnace: Model LC-RF2-14TP (Shanghai Lichen Bangxi Instrument Technology Co., Ltd.), temperature control accuracy ±5℃; Laser particle size analyzer: Model LA950 (Horiba, Japan), detection range 0.01-3500μm; X-ray fluorescence spectrometer (XRF): Model Axiosmax (Panaco), detection limit 0.001%.

[0021] Abnormal situation handling plan: Abnormal situation 1: Freezing temperature did not reach -70℃. Countermeasures: Extend the freezing time to 70 minutes, or lower the cold trap temperature to -80℃ to ensure the colloid is completely frozen.

[0022] Abnormal situation 2: Vacuum fluctuation exceeds ±5Pa during vacuum sublimation drying. Countermeasures: Suspend drying, check for aging of equipment seals (such as silicone rings), replace them, re-evacuate to the set range, and then continue drying.

[0023] Abnormal situation 3: The agglomeration rate of powder after calcination exceeds the standard (>30%). Countermeasures: Increase the calcination temperature by 10°C from 900°C, or extend the calcination time by 1 hour to further disperse the particles through high temperature. Example 1

[0024] A method for preparing tin dioxide powder with anti-agglomeration properties of tin hydroxide by freeze-drying involves dissolving 50g of sodium stannate in deionized water and diluting it to 1L to obtain a tin source solution with a concentration of 50g / L; dissolving 5g of oxalic acid in deionized water and diluting it to 1L to obtain a precipitant solution with a concentration of 5g / L (mass ratio of tin source solution to precipitant solution 1:0.1); adding the precipitant solution dropwise to the tin source solution at a rate of 1.5mL / min under constant temperature magnetic stirring at 28℃ and 400r / min to generate tin hydroxide colloid; stirring for 2 hours after reaction; and allowing to stand for aging for 24 hours to allow the colloidal particles to be distributed in the range of 50-100nm. The aged colloid is then transferred to a polytetrafluoroethylene container and rapidly frozen in an ultra-low temperature cold trap at -75℃ for 45min. The frozen colloid was then transferred to a vacuum freeze-drying oven for vacuum sublimation drying at -50℃ and 15Pa for 36 hours to obtain loose tin hydroxide dry powder. The microstructure of this dry powder is as follows. Figure 1 As shown in the scanning electron microscope (SEM) images, the powder exhibits an irregular flocculent structure without significant agglomeration. The four representative particles marked in the image (65nm, 73nm, 78nm, and 82nm) all fall within the defined size range of 50-100nm, verifying the effectiveness of the colloidal preparation steps. Subsequent calcination treatment involved placing the dried powder in an alumina crucible and calcining it at 900℃ for 4 hours (in an air atmosphere with an oxygen content greater than 20%) to finally obtain tin dioxide powder. Example 2

[0025] A freeze-drying method for preparing tin dioxide powder to inhibit tin hydroxide agglomeration involves dissolving 48g of sodium stannate in deionized water and diluting it to 1L to obtain a tin source solution with a concentration of 48g / L; dissolving 8g of oxalic acid in deionized water and diluting it to 1L to obtain a precipitant solution with a concentration of 8g / L (the mass ratio of tin source solution to precipitant solution is 1:0.167); adding the precipitant solution dropwise to the tin source solution at a rate of 2mL / min under constant temperature magnetic stirring at 30℃ and 450r / min to react and generate a colloid; stirring for 2.5h after reaction; and allowing it to stand for 24h to age, so that the particle size distribution of the colloidal particles is in the range of 60-100nm. The aged colloid is then transferred to a polytetrafluoroethylene container and rapidly frozen in an ultra-low temperature cold trap at -78℃ for 50min. The frozen colloid was then transferred to a vacuum freeze dryer for vacuum sublimation drying at -48℃ and 15Pa for 40 hours to obtain loose tin hydroxide dry powder. The tin hydroxide dry powder dried in step (3) was placed in a muffle furnace and calcined at 900±20℃ for 3-5 hours to obtain tin dioxide powder. Subsequent calcination treatment was performed by placing the dried powder in an alumina crucible and calcining it at 880℃ for 5 hours (in an air atmosphere with an oxygen content greater than 25%) to finally obtain tin dioxide powder. Example 3

[0026] A method for preparing tin dioxide powder with anti-agglomeration properties of tin hydroxide by freeze-drying involves dissolving 42g of sodium stannate in deionized water and diluting it to 1L to obtain a tin source solution with a concentration of 42g / L; dissolving 8.4g of oxalic acid in deionized water and diluting it to 1L to obtain a precipitant solution with a concentration of 8.4g / L (mass ratio of tin source solution to precipitant solution 1:0.2); adding the precipitant solution dropwise to the tin source solution at a rate of 1mL / min under constant temperature magnetic stirring at 25℃ and 500r / min to react and generate a colloid; stirring for another 2 hours after the reaction; and allowing the mixture to stand for 24 hours to age, allowing the colloidal particles to be distributed in the range of 50-100nm. The aged colloid is then transferred to a polytetrafluoroethylene container and rapidly frozen in an ultra-low temperature cold trap at -70℃ for 60min. The frozen icy colloid was then transferred to a vacuum freeze-drying oven for vacuum sublimation drying at -52℃ and 20Pa for 24 hours to obtain loose tin hydroxide dry powder. Subsequent calcination treatment involved placing the dried powder in an alumina crucible and calcining it at 910℃ for 4 hours (in an air atmosphere with an oxygen content greater than 20%) to finally obtain tin dioxide powder. Example 4

[0027] A method for preparing tin dioxide powder with anti-agglomeration properties of tin hydroxide by freeze-drying involves dissolving 48g of sodium stannate in deionized water and diluting it to 1L to obtain a tin source solution with a concentration of 48g / L; dissolving 7.2g of oxalic acid in deionized water and diluting it to 1L to obtain a precipitant solution with a concentration of 7.2g / L (mass ratio of tin source solution to precipitant solution 1:0.15); adding the precipitant solution dropwise to the tin source solution at a rate of 2mL / min under constant temperature magnetic stirring at 30℃ and 300r / min to react and generate a colloid; stirring for another 2 hours after the reaction; and allowing the mixture to stand for 24 hours to age, allowing the colloidal particles to be distributed in the range of 50-100nm. The aged colloid is then transferred to a polytetrafluoroethylene container and rapidly frozen in an ultra-low temperature cold trap at -73℃ for 30 minutes. The frozen colloid was then transferred to a vacuum freeze-drying oven for vacuum sublimation drying at -48℃ and 10Pa for 48 hours to obtain loose tin hydroxide dry powder. Subsequent calcination was performed by placing the dried powder in an alumina crucible and calcining it at 920℃ for 3 hours (in an air atmosphere with an oxygen content greater than 25%) to finally obtain tin dioxide powder. Example 5

[0028] A method for preparing tin dioxide powder with inhibitory tin hydroxide agglomeration by freeze-drying involves dissolving 36g of sodium stannate in deionized water and diluting it to 1L to obtain a tin source solution with a concentration of 36g / L. 9g of oxalic acid is dissolved in deionized water and diluted to 300mL to obtain a precipitant solution with a concentration of 30g / L (the mass ratio of tin source solute to precipitant solute is 1:0.25). Under constant temperature magnetic stirring at 25℃ and 300r / min, the precipitant solution is added dropwise to the tin source solution at a rate of 1mL / min. The reaction is carried out for 2 hours, followed by stirring for another 2 hours, and then allowed to stand for 24 hours to allow the colloidal particles to be distributed in the range of 50–100nm. The aged colloid is then transferred to a polytetrafluoroethylene container and rapidly frozen in a -75℃ ultra-low temperature cold trap for 60min. The frozen colloid was then transferred to a vacuum freeze-drying oven for vacuum sublimation drying: dried at -50℃ and 15Pa for 48 hours to obtain loose tin hydroxide dry powder. Subsequent calcination treatment was performed by placing the dried powder in an alumina crucible and calcining it at 900℃ in air (oxygen content greater than 20%) for 5 hours to finally obtain tin dioxide powder. Example 6

[0029] A freeze-drying method for preparing tin dioxide powder to inhibit tin hydroxide agglomeration involves dissolving 54 g of sodium stannate in deionized water and diluting it to 1 L to obtain a tin source solution with a concentration of 54 g / L. 5.4 g of oxalic acid is dissolved in deionized water and diluted to 1 L to obtain a precipitant solution with a concentration of 5.4 g / L (the mass ratio of tin source solute to precipitant solute is 1:0.1). Under constant temperature magnetic stirring at 30℃ and 500 r / min, the precipitant solution is added dropwise to the tin source solution at a rate of 2 mL / min. After reacting for 2 h, stirring is continued for another 2 h, followed by aging for 24 h. The colloidal particle size distribution is in the range of 50-100 nm. The aged colloid is then transferred to a polytetrafluoroethylene container and rapidly frozen in a -75℃ ultra-low temperature cold trap for 30 min. The frozen colloid was then transferred to a vacuum freeze-drying oven for vacuum sublimation drying at -50℃ and 15Pa for 24 hours to obtain loose tin hydroxide dry powder. Subsequent calcination treatment involved placing the dried powder in an alumina crucible and calcining it at 900℃ in air (oxygen content greater than 25%) for 3 hours to finally obtain tin dioxide powder.

[0030] The conductivity of the deionized water used in the above embodiments is ≤10μS / cm.

[0031] Comparative Example 1: Traditional Oven Drying Method This comparative example aims to compare the effectiveness of conventional oven drying and the drying technology of this invention in suppressing the agglomeration of tin hydroxide.

[0032] The method for preparing tin hydroxide colloid is exactly the same as in Example 1. The aged tin hydroxide colloid is transferred to a glass container and dried in an oven at 80°C and normal pressure for 12 hours to obtain tin hydroxide dry powder (without freezing). The calcination treatment is the same as in Example 1 to obtain tin dioxide powder.

[0033] Comparative Example 2: Conventional freeze-drying method This comparative example aims to compare the effectiveness of conventional cryogenic freezing and the ultra-low temperature rapid freezing of the present invention in suppressing tin hydroxide agglomeration.

[0034] The method for preparing tin hydroxide colloid was exactly the same as in Example 1. The aged tin hydroxide colloid was transferred to a polytetrafluoroethylene container and placed in a BCD-216SDN type conventional freezer. It was frozen at -20°C for 12 hours to completely freeze the colloid into an ice state. The frozen colloid was then dried using the same method as in Example 1. The frozen colloid was transferred to a YTLG-10A type freeze dryer and vacuum sublimated at -50°C and 15 Pa for 36 hours to obtain dry tin hydroxide powder. This powder was then calcined using the same method as in Example 1.

[0035] The particle size, purity, and agglomeration rate of the tin dioxide powders obtained in the above examples and comparative examples were tested. Particle size was determined using GB / T 19077-2016 "Particle Size Distribution - Laser Diffraction Method", purity was determined using JY / T015-1996 "General Rules for Inductively Coupled Plasma Atomic Emission Spectroscopy", and agglomeration rate was determined using the sedimentation method. The results are shown in the table below:

[0036] The test results fully verify the superiority of the present invention. Specifically, the particle size distribution of the tin dioxide powder obtained in Example 1 is as follows: Figure 2 As shown in the figure, 'D50=95nm' indicates that the median particle size of the powder is 95nm, falling within the defined range of 80-120nm. This is completely consistent with the particle size detection data of Example 1 in the table, which directly proves that the tin dioxide powder prepared by the method of this invention has a uniform and controllable particle size distribution. The results of Comparative Example 2 are particularly crucial, showing that even if the same sublimation drying parameters and the same mass ratio are used as in this invention, if the initial freezing stage only uses conventional freezing at -20℃, its agglomeration inhibition effect will be greatly reduced (agglomeration rate 34.7%), which is far inferior to that of this invention (<10%). This proves that the "mass ratio control" in step (1), the "ultra-low temperature rapid freezing" in step (2), and the "low temperature high vacuum sublimation drying" in step (3) are a tightly coupled and synergistic organic whole.

[0037] Figure 3Comparative images show the physical appearance of tin hydroxide dry powder prepared by conventional oven drying (Comparative Example 1) and conventional freeze drying (Comparative Example 2) with that obtained by the method of the present invention (Example 1). As can be seen from the images, the tin hydroxide dry powder prepared by the method of the present invention exhibits no agglomeration, while the tin hydroxide dry powders obtained by Comparative Examples 1 and 2 show severe agglomeration.

[0038] The specific parameter combination of the present invention achieves a good connection between "preparing stable colloids", "rapidly fixing the dispersion structure" and "completely avoiding liquid phase regeneration", producing technical effects that cannot be achieved by a single technical means or simple parameter superposition, and effectively solving the technical problems existing in the field.

Claims

1. A method for preparing tin dioxide powder by freeze-drying to inhibit tin hydroxide agglomeration, characterized in that, Includes the following steps: (1) Preparation of tin hydroxide colloid: Sodium stannate is dissolved in deionized water with a conductivity ≤10μS / cm to prepare a tin source solution with a concentration of 36-54g / L; oxalic acid is dissolved in deionized water with a conductivity ≤10μS / cm to prepare a precipitant solution with a concentration of 5-30g / L; the mass ratio of tin source solution to precipitant solution is controlled at 1:0.1-0.25; under constant temperature magnetic stirring, the precipitant solution is added dropwise to the tin source solution at a rate of 1-2mL / min, the reaction temperature is controlled at 25-30℃, the stirring speed is controlled at 300-500r / min, and tin hydroxide colloid is generated by the reaction; after the reaction is completed, stirring is continued for at least 2h, and the mixture is allowed to stand for at least 24h to age, and the particle size of the colloid is controlled at 50-100nm; (2) Ultra-low temperature rapid freezing treatment: Transfer the aged tin hydroxide colloid in step (1) to a freezing container and place it in a cold trap at ≤-70℃±2℃ for rapid freezing for 30-60 minutes to freeze the colloid into an ice state instantly, thereby inhibiting the particle extrusion and agglomeration caused by ice crystal growth; (3) Low-temperature vacuum sublimation drying: The ice colloid after freezing in step (2) is transferred to a freeze dryer and sublimated at a temperature of -50℃±2℃ and a vacuum of 15±5Pa for 24-48h, so that the ice crystals sublimate directly, avoiding the generation of liquid phase during the drying process, and obtaining loose tin hydroxide dry powder. (4) Calcination treatment: The dry tin hydroxide powder after step (3) is placed in a muffle furnace and calcined at 900±20℃ for 3-5 hours to obtain tin dioxide powder.

2. The method for preparing tin dioxide powder by freeze-drying to inhibit tin hydroxide agglomeration according to claim 1, characterized in that, The rapid freezing described in step (2) has a freezing rate of ≥10℃ / min.

3. The method for preparing tin dioxide by freeze-drying to inhibit tin hydroxide agglomeration according to claim 1, characterized in that, The freezing container mentioned in step (2) is a polytetrafluoroethylene container.

4. The method for preparing tin dioxide powder by freeze-drying to inhibit tin hydroxide agglomeration according to claim 1, characterized in that, In step (4), the calcination environment inside the muffle furnace is an air atmosphere with an oxygen content of ≥20%.

Citation Information

Patent Citations

  • Wet-to-dry dispersant-free method for producing ultrafine nanoscale dry powder and involved device

    CN103263963A

  • Preparation method of graphene-tin dioxide nanoparticle three-dimensional foam composite material

    CN103482616B

  • Preparation method of a graphene aerogel supported tin dioxide composite material

    CN104143631B

  • Preparation method of ultra-dispersed ITO powder

    CN114314642A

  • Preparation method for efficiently dispersing SnO2

    CN115974139A